(untitled) (Medico Legal Update, 2020)
Background/Objectives: The purpose of this study is to suggest the policy task and direction so that the projects for women-friendly city can level by analyzing Dangjin City’s women-friendly city building process, by suggesting the Dangjin City’s vision and road map for the women-friendly city. Method/Statistical Analysis: The research conducted trend analysis, questionnaire survey and FGI. For this purpose, we surveyed , 800 citizens (about 0.5% of Dangjin 166,000) were taken as sampling frame and through the quota sampling frame by gender, age and area, total 782 questionnaires (final effective ratio 97.8%) were collected and utilized for analysis. FGI was conducted through 22 people from three groups of citizens, experts and officials. Findings: As a result, we set up our vision of ‘Because woman is happy, your family is happy, your Dangjin’, For this vision, 4 major goals of ‘Diffusion of citizen’s feeling on the women-friendly city’, ‘Building safety city to live comfortably’, ‘Building the human-oriented employment environment’, ‘Inter-regional shared growth without alienation’ were established. Improvements/Applications: The women-friendly city in Korea, it requires the policy direction to establish the policy reflected with regional characteristics and step-by-step and feasible policy sharing with the local resident.